Eksistensi paguyuban masyarakat perantau dalam mempererat persaudaraan - Sitorus, Yalizar Rahayu; Anwar, Muhammad Syaiful; Maulana, Fikri; Winika, Tiara Resti; Mulyawati, Husni (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
One of the negative impacts of the bad environment on people who live in metropolitan cities is individualism that can damage brotherhood’s values. This study aims to analyze the existence of the migrants’s paguyuban in strengthening the brotherhood of its members. The paguyuban in this research is the ‘Ikatan Keluarga Balingka’ (IKB) which is located in Medan. Balingka is one of village in West Sumatera. This study was employed a qualitative approach with data collected through observation, interviews, and documentation. The results showed that the existence of the IKB Medan can be found when it is used as communication forum. The close brotherhood of migrants in IKB Medan can be seen when they get to know each other, feel the sensation of being in their hometown, and care for each other. So, efforts are needed to preserve local brotherhood to support national unity.